PERTANGGUNGJAWABAN PIDANA TERHADAP BADAN USAHA SEBAGAI PELAKU TINDAK PIDANA GANGGUAN FUNGSI JALAN - Anggara, Ario; Ukas, Ukas (SCIENTIA JOURNAL, 2019)
The number of types of road disruption one of them, namely the use of speed limiting tools. Speed limiting equipment must always refer to Kepmenhub Number KM. 3 of 1994. There are still many who make speed limiting devices dont in accordance with the rules and result in the failure of road functions. Regarding the perpetrators regulated in Article 28 Paragraph (1) UULLAJ and the criminal sanctions are regulated in Article 274 Paragraph (1). The rule is only people regulating individuals not business entities. Formulation of the problem in this study is how criminal liability of business entities as perpetrators of crimes which results in disruption of road functions and whether the criminal sanctions applied in the UULLAJ in accordance with objectives of the law. Purpose of this study is to determine the criminal liability of business entities as perpetrators crimes that result in disruption of road functions and to find out the criminal sanctions applied in the UULLAJ in accordance with the objectives of the law. This type of research is normative legal research or library legal research methods. Business entities cannot be held accountable for crimes because the UULLAJ does not regulate this. Provisions of criminal sanctions applied in the UULLAJ against perpetrators of road disruption contained in Article 28 paragraph (1) Jo Article 274 paragraph (1) do not accommodate sense of justice, this is because in the phrase everyone refers only to the legal subject of individuals.